High-heat-resistance aluminum hydroxide micro powder as well as preparation method and application thereof
Through wet grinding and species decomposition reaction, combined with ammonium salt dispersant, high heat-resistant aluminum hydroxide fine powder was prepared, which solved the problem of easy decomposition of existing aluminum hydroxide fine powder at high temperatures, and achieved higher heat resistance and The stability in the manufacturing of copper clad plate has achieved the effect of import substitution.
Patent Information
- Application Number
- CN202411207368.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-14
AI Technical Summary
Existing aluminum hydroxide fine powder is easy to decompose at high temperatures, resulting in layered explosive plates during the processing of copper clad plates, affecting product quality.
The seed crystals are prepared by wet grinding method, and the seed decomposition reaction is carried out in sodium aluminate solution. The ammonium salt dispersant is added to improve dispersion and heat resistance. By controlling the reaction conditions such as temperature and stirring rate, the particle size is uniform and High heat-resistant aluminum hydroxide powder.
The heat resistance of aluminum hydroxide micro powder is significantly improved, and the 2% water loss temperature exceeds 257℃. It achieves higher heat resistance and product stability in the manufacturing of copper clad plates, replacing imported micro powders.
Smart Images

Figure CN119306236A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum hydroxide micropowder preparation, and specifically relates to high-heat-resistant aluminum hydroxide micropowder and a preparation method and application thereof. Background Art
[0002] The demand for micronized aluminum hydroxide for special cables and copper-clad laminates in my country is about 30,000 tons per year, and it is expected to grow at an annual rate of 8-10% in the future. Copper-clad laminates need to be operated at high temperatures (250-260°C) in the later process of making circuit boards. The heat resistance of aluminum hydroxide will affect the heat resistance of copper-clad laminates. If the heat resistance is poor, aluminum hydroxide will be more likely to decompose and release water molecules at high temperatures, which will cause the copper-clad laminates to delaminate and explode during processing, resulting in product scrapping.
[0003] The existing technology mostly adopts the seed decomposition method to prepare aluminum hydroxide micropowder. The aluminum hydroxide micropowder prepared by the existing seed decomposition method has poor heat resistance and is easily decomposed at high temperatures, which limits its application in some high-temperature environments. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a high heat-resistant aluminum hydroxide micropowder and a preparation method and application thereof. The present invention specifically includes the following contents:
[0005] A method for preparing high heat-resistant aluminum hydroxide micropowder comprises the following steps:
[0006] S1, preparing seed crystals: mixing aluminum hydroxide powder with water to prepare a slurry, adding an ammonium salt dispersant accounting for 0.1-0.3% of the weight of aluminum hydroxide to the slurry, and then wet grinding to obtain a seed crystal slurry with a particle size D50=0.6-1.3μm and a solid content of 180-210g / L; the role of adding ammonium salt is to act as a dispersant, which can increase the dispersibility of the seed crystals during grinding, making the seed crystals more uniform in particle size, and can further increase the dispersibility of the seed crystals in the subsequent reaction system, making the reaction more uniform, and the particle size of the obtained product more uniform;
[0007] S2, seed decomposition reaction: to Al 2 O 3 Add the seed slurry to a sodium aluminate solution with a concentration of 100-115 g / l and an αk of 1.45-1.65, stir, and perform a seed decomposition reaction, controlling the seed ratio to 1.1%-1.3%, the stirring rate to 400-600 rpm, the decomposition temperature to 70-75°C, and the reaction time to 24-26 hours;
[0008] S3, post-treatment: filtering and washing the slurry after the seed decomposition reaction, then adding an ammonium salt dispersant accounting for 0.1-0.3% of the mass of aluminum hydroxide, stirring evenly and drying to obtain the high heat-resistant aluminum hydroxide micropowder, wherein the 2% water loss temperature of the high heat-resistant aluminum hydroxide micropowder is greater than 257°C. The role of adding the ammonium salt before drying is to act as a dispersant, which can effectively prevent the aluminum hydroxide micropowder from agglomerating during the drying process, increase the dispersibility of the product, and further improve the heat resistance. The ammonium salt can be a polycarboxylate ammonium salt dispersant, an acrylate copolymer ammonium salt dispersant, other ammonium salt polymer dispersants, etc.
[0009] Preferably, the wet grinding method is: using two sanding machines in two stages connected in series to perform wet mechanical grinding on the slurry.
[0010] Preferably, the decomposition rate of the seed decomposition reaction is 52-57%.
[0011] Preferably, the high heat-resistant aluminum hydroxide micropowder has a particle size D50 of 1.5-2.5 μm, an electrical conductivity of <30 us / cm, and a sodium oxide content of <0.13 wt%.
[0012] A high heat-resistant aluminum hydroxide micropowder prepared by adopting the method for preparing the high heat-resistant aluminum hydroxide micropowder.
[0013] An application of the highly heat-resistant aluminum hydroxide micropowder in copper-clad laminates.
[0014] Beneficial effects of the present invention:
[0015] (1) The method of the present invention uses the sodium aluminate solution produced in the process of producing alumina by sintering, that is, the sodium aluminate solution refined by the processes of batching, sintering, dissolution, desiliconization, leaf filtration, etc. of ore, limestone, raw coal, soda ash, etc. as the raw material, adopts the grinding method seed, and the directional induced decomposition process to make the crystal inert growth, strengthen the single crystal growth of aluminum hydroxide particles, and effectively reduce the content of sodium oxide coated between crystals.
[0016] (2) The present invention adds an ammonium salt dispersant during the seed preparation stage, so that the prepared seed crystals have finer and more uniform particle size, and better dispersibility in the later reaction system. The particle size distribution of the decomposed and grown micro-powder aluminum hydroxide is narrow and uniform, and its D97 is ≤5μm, and the content of particles greater than 45μm is ≤20ppm. The present invention also adds an ammonium salt dispersant to the washed aluminum hydroxide. Under the same particle size, the aluminum hydroxide crystals prepared by the present invention have perfect morphology, high dispersibility, and low sodium oxide content, so that they have higher heat resistance, and the 2% water loss temperature is ≥257°C, which has achieved import substitution in the high-end micro-powder aluminum hydroxide industry for copper clad laminates. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1The SEM image of the high heat-resistant aluminum hydroxide powder prepared by the method of the present invention is shown in FIG. DETAILED DESCRIPTION
[0018] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments shown below do not limit the invention content described in the claims. In addition, the entire contents of the structures represented by the following embodiments are not limited to those necessary as solutions to the invention described in the claims.
[0019] A method for preparing high heat-resistant aluminum hydroxide micropowder comprises the following steps:
[0020] S1, preparing seed crystals: mixing aluminum hydroxide powder with water to prepare a slurry, adding an ammonium salt dispersant accounting for 0.1-0.3% of the weight of aluminum hydroxide to the slurry, and then using two grinding machines in two stages connected in series to wet mechanically grind the slurry to obtain a seed crystal slurry with a particle size D50 = 0.6-1.3 μm and a solid content of 180-210 g / L;
[0021] S2, seed decomposition reaction: to Al 2 O 3 The seed slurry is added to a sodium aluminate solution with a concentration of 100-115 g / l and an αk of 1.45-1.65, and stirred to carry out a seed decomposition reaction, wherein the seed ratio is controlled to be 1.1%-1.3%, the stirring rate is 400-600 rpm, the decomposition temperature is 70-75° C., and the reaction time is 24-26 h; the decomposition rate of the seed decomposition reaction is 52-57%;
[0022] S3, post-treatment: filter and wash the slurry after the seed decomposition reaction, then add 0.1-0.3% of the mass of aluminum hydroxide ammonium salt dispersant, stir evenly and dry to obtain the high heat-resistant aluminum hydroxide powder (see attached Figure 1 ), the 2% dehydration temperature of the high heat-resistant aluminum hydroxide micropowder is greater than 257°C; the particle size D50 of the high heat-resistant aluminum hydroxide micropowder is 1.5-2.5μm, the electrical conductivity is less than 30us / cm, and the sodium oxide content is less than 0.13wt%.
[0023] Example 1
[0024] S1, mix aluminum hydroxide powder with D50=2.1~2.4μm with distilled water to prepare slurry, add ammonium salt dispersant accounting for 0.1% of the weight of aluminum hydroxide into the slurry, and then use two 60L sand mills in two stages in series to wet mechanically grind the slurry to obtain a seed slurry with a particle size of D50=0.6μm and a solid content of 180g / l.
[0025] S2, first add a precisely measured sodium aluminate solution (Al 2 O3 The concentration is 100g / l, αk is 1.45), then the seed slurry is added and stirred, the stirring rate is 400rpm, the overall seed ratio is 1.1%, the decomposition temperature is 70℃, the decomposition time is 24 hours, and after the decomposition is completed, it enters the storage tank;
[0026] S3, the decomposed slurry in the storage tank is filtered and washed, and then 0.1% of the mass of aluminum hydroxide is added as an ammonium salt dispersant, stirred evenly and dried, and then dried to obtain an aluminum hydroxide micropowder industrial product with D50=2.5μm, conductivity=26us / cm, sodium oxide content of 0.08%, and 2% water loss temperature of 260°C.
[0027] Example 2
[0028] S1, mix aluminum hydroxide powder with D50=2.1~2.4μm with distilled water to prepare slurry, add ammonium salt dispersant accounting for 0.3% of the weight of aluminum hydroxide into the slurry, and then use two 60L sand mills in two stages in series to wet mechanically grind the slurry to obtain a seed slurry with a particle size of D50=1.3μm and a solid content of 210g / l.
[0029] S2, first add a precisely measured sodium aluminate solution (Al 2 O 3 The concentration is 115g / l, αk is 1.65), then the seed slurry is added and stirred, the stirring rate is 600rpm, the overall seed ratio is 1.3%, the decomposition temperature is 75℃, the decomposition time is 226 hours, and after the decomposition is completed, it enters the storage tank;
[0030] S3, the decomposed slurry in the storage tank is filtered and washed, and then 0.3% of the mass of aluminum hydroxide is added as an ammonium salt dispersant, stirred evenly and dried, and then dried to obtain an aluminum hydroxide micropowder industrial product with D50=1.5μm, conductivity=23us / cm, sodium oxide content of 0.11%, and 2% water loss temperature of 265°C.
[0031] Example 3
[0032] S1, mix aluminum hydroxide powder with D50=2.1~2.4μm with distilled water to form a slurry, add ammonium salt dispersant accounting for 0.15% of the weight of aluminum hydroxide into the slurry, and then use two 60L sand mills in two stages in series to wet mechanically grind the slurry to obtain a seed slurry with a particle size of D50=1.0μm and a solid content of 200g / l.
[0033] S2, first add a precisely measured sodium aluminate solution (Al 2 O 3The concentration is 110g / l, αk is 1.55), then the seed slurry is added and stirred, the stirring rate is 500rpm, the overall seed ratio is 1.2%, the decomposition temperature is 72-74℃, the decomposition time is 25 hours, and after the decomposition is completed, it enters the storage tank;
[0034] S3, the decomposed slurry in the storage tank is filtered and washed, and then 0.2% of the mass of aluminum hydroxide is added as an ammonium salt dispersant, stirred evenly and dried, and then dried to obtain an aluminum hydroxide micropowder industrial product with D50=1.9μm, conductivity=19us / cm, sodium oxide content of 0.07%, and 2% water loss temperature of 268°C.
[0035] Example 4
[0036] S1, mix aluminum hydroxide powder with D50=2.1~2.4μm with distilled water to prepare slurry, add ammonium salt dispersant accounting for 0.2% of the weight of aluminum hydroxide into the slurry, and then use two 60L sand mills in two stages in series to wet mechanically grind the slurry to obtain a seed slurry with a particle size of D50=0.8μm and a solid content of 190g / l.
[0037] S2, first add a precisely measured sodium aluminate solution (Al 2 O 3 The concentration is 105g / l, αk is 1.5), then the seed slurry is added and stirred, the stirring rate is 550rpm, the overall seed ratio is 1.2%, the decomposition temperature is 70-73℃, the decomposition time is 25 hours, and after the decomposition is completed, it enters the storage tank;
[0038] S3, the decomposed slurry in the storage tank is filtered and washed, and then 0.25% of the mass of the aluminum hydroxide is added with an ammonium salt dispersant, stirred evenly and dried to obtain an aluminum hydroxide micropowder industrial product with D50 = 2.0 μm, conductivity = 18 us / cm, sodium oxide content of 0.06wt%, and 2% water loss temperature reaching 271°C.
[0039] Comparative Example 1
[0040] The difference between this comparative example and Example 4 is that no ammonium salt is added during the preparation of the seed crystals and after washing, and other conditions are the same.
[0041] The aluminum hydroxide powder prepared in this comparative example has a D50 of 2.1 μm, a conductivity of 24 us / cm, a sodium oxide content of 0.08 wt%, and a 2% dehydration temperature of 230° C. It can be seen that the heat resistance of the aluminum hydroxide powder prepared in this comparative example is worse than that of Example 4.
[0042] Comparative Example 2
[0043] The difference between this comparative example and Example 4 is that the amount of the ammonium salt dispersant added during the preparation of the seed crystals and after washing is 0.4%, and the other conditions are the same.
[0044] The aluminum hydroxide powder prepared in this comparative example has a D50 of 1.6 μm, a conductivity of 34 us / cm, a sodium oxide content of 0.09 wt%, and a 2% dehydration temperature of 241° C. It can be seen that the heat resistance of the aluminum hydroxide powder prepared in this comparative example is worse than that of Example 4.
[0045] Comparative Example 3
[0046] The difference between this comparative example and Example 4 is that D50 of the seed crystal is 0.5 μm, and other conditions are the same.
[0047] The aluminum hydroxide powder prepared in this comparative example has a D50 of 1.5 μm, a conductivity of 32 us / cm, a sodium oxide content of 0.18 wt%, and a 2% water loss temperature of 198° C. It can be seen that the aluminum hydroxide powder prepared in this comparative example has a higher sodium oxide content and poorer heat resistance.
[0048] Comparative Example 4
[0049] The difference between this comparative example and Example 4 is that the seed ratio is 1.0%, and other conditions are the same.
[0050] The aluminum hydroxide powder prepared in this comparative example has a D50 of 2.7 μm, a conductivity of 17 us / cm, a sodium oxide content of 0.13 wt%, and a 2% water loss temperature of 211° C. It can be seen that the aluminum hydroxide powder prepared in this comparative example has poor heat resistance.
[0051] Comparative Example 5
[0052] The difference between this comparative example and Example 4 is that the decomposition temperature is 80° C. and the stirring speed is 300 rpm, and the other conditions are the same.
[0053] The aluminum hydroxide powder prepared in this comparative example has a D50 of 3.3 μm, a conductivity of 16 us / cm, a sodium oxide content of 0.17 wt%, and a 2% water loss temperature of 203° C. It can be seen that the aluminum hydroxide powder prepared in this comparative example has poor heat resistance.
[0054] Comparative Example 6
[0055] The difference between this comparative example and Example 4 is that the decomposition temperature is 60° C. and the stirring speed is 700 pm, and the other conditions are the same.
[0056] The aluminum hydroxide powder prepared in this comparative example has a D50 of 1.3 μm, a conductivity of 35 us / cm, a sodium oxide content of 0.21 wt%, and a 2% water loss temperature of 184° C. It can be seen that the aluminum hydroxide powder prepared in this comparative example has poor heat resistance.
[0057] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing high heat-resistant aluminum hydroxide micropowder, characterized in that: The following steps are involved: S1, preparing seed crystals: mixing aluminum hydroxide powder with water to prepare a slurry, adding an ammonium salt dispersant accounting for 0.1-0.3% of the weight of aluminum hydroxide to the slurry, and then wet grinding to obtain a seed crystal slurry with a particle size D50 = 0.6-1.3 μm and a solid content of 180-210 g / L; S2, seed decomposition reaction: adding the seed slurry to a sodium aluminate solution with an Al2O3 concentration of 100-115 g / l and an αk of 1.45-1.65, and stirring to carry out a seed decomposition reaction, controlling the seed ratio to 1.1%-1.3%, the stirring rate to 400-600 rpm, the decomposition temperature to 70-75°C, and the reaction time to 24-26 h; S3, post-treatment: filter and wash the slurry after the seed decomposition reaction, then add 0.1-0.3% of the mass of aluminum hydroxide ammonium salt dispersant, stir evenly and dry to obtain the high heat-resistant aluminum hydroxide micropowder, the 2% water loss temperature of the high heat-resistant aluminum hydroxide micropowder is greater than 257°C.
2. The method for preparing a high heat-resistant aluminum hydroxide micropowder according to claim 1, characterized in that: The wet grinding method comprises: using two sanding machines connected in series at two stages to perform wet mechanical grinding on the slurry.
3. The method for preparing a high heat-resistant aluminum hydroxide micropowder according to claim 1, characterized in that: The decomposition rate of the seed decomposition reaction is 52-57%.
4. The method for preparing the high heat-resistant aluminum hydroxide powder according to any one of claims 1 to 3, characterized in that: The high heat-resistant aluminum hydroxide micropowder has a particle size D50 of 1.5-2.5 μm, an electrical conductivity of less than 30 us / cm, and a sodium oxide content of less than 0.13 wt%.
5. A high heat-resistant aluminum hydroxide micropowder prepared by the method for preparing high heat-resistant aluminum hydroxide micropowder according to any one of claims 1 to 4.
6. Use of the high heat-resistant aluminum hydroxide powder according to claim 5 in copper-clad laminates.